2015
DOI: 10.5535/arm.2015.39.3.384
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fat Mass Percentage and Body Mass Index in Koreans With Spinal Cord Injury According to the Severity and Duration of Motor Paralysis

Abstract: ObjectiveTo analyze the relationship of the change in fat mass percentage (FMP) and body mass index (BMI) with the change in obesity rate according to gender, extent of spinal cord injury (SCI) and the duration.MethodsThe retrospective study was conducted with medical records of 915 patients. FMP was calculated with BMI and bioelectrical impedance analysis (BIA). Statistical analysis of the relationship between FMP and gender, extent of SCI and the duration after SCI was done.ResultsFMP increased in relation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…A lower total lean body mass in individuals with a spinal cord injury compared to able-bodied controls was found (3,4,29). Fat mass revealed a good correlation with the duration of the injury (30,31). Furthermore, the total body fat percentage was compared to the Body-Mass-Index (BMI), whereas McDonald et al (28) suggested that BMI underestimated obesity in this population.…”
Section: Body Composition In Individuals With a Spinal Cord Injurymentioning
confidence: 99%
“…A lower total lean body mass in individuals with a spinal cord injury compared to able-bodied controls was found (3,4,29). Fat mass revealed a good correlation with the duration of the injury (30,31). Furthermore, the total body fat percentage was compared to the Body-Mass-Index (BMI), whereas McDonald et al (28) suggested that BMI underestimated obesity in this population.…”
Section: Body Composition In Individuals With a Spinal Cord Injurymentioning
confidence: 99%
“…Individuals with tetraplegia had lower mean BMI compared to individuals with paraplegia (weighted mean difference (WMD) −0.9 kg/m 2 , 95% confidence interval (CI) −1.4, −0.5; I 2 86.5%) (Table 2). This was based on 32 [13][14][15][16][31][32][33][34][35]37,40,41,43,[45][46][47][48][49][51][52][53][54][55][57][58][59][60][61][62][63]65,76,77] out of 36 studies comparing tetraplegia and paraplegia, which comprised 3837 participants. We found no differences when comparing high and low paraplegia (WMD −0.2, 95% CI −1.0, 0.5; I 2 22.7%) (Table 2).…”
Section: Anthropometric Measuresmentioning
confidence: 99%
“…Eleven studies [13][14][15][16]35,36,39,40,43,48,76], which included 1386 participants, were included in the meta-analysis of total body composition to compare tetraplegia and paraplegia (Table 2). Whole-body composition was estimated through various methods.…”
Section: Total Body Compositionmentioning
confidence: 99%
See 2 more Smart Citations